2020
DOI: 10.1111/aab.12613
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci mapping of adult‐plant resistance to powdery mildew in triticale

Abstract: Powdery mildew (PM) is a common disease caused by Blumeria graminis, which affects cereals and has recently adapted to triticale. Adult‐plant resistance (APR) genes provide durable protection of crops from the disease. Quantitative trait loci corresponding to the APR effects were mapped in an F2 population of “Lamberto” (susceptible) × “Moderto” (resistant). A genetic map of winter triticale was constructed based on the segregation of 863 DArT, 38 microsatellite and 10 resistance gene analogue markers. Composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 49 publications
3
24
0
Order By: Relevance
“…Magnat Abbreviations: ABS/CS, absorbed energy flux per leaf cross-section (CS); Tr 0 /CS, trapped energy flux in PSII reaction centers per leaf crosssection; ET 0 /CS, the energy flux for electron transport per leaf cross-section; ET 0 /RC, the energy flux for electron transport per the single, active PSII reaction center; F v /F m , yield of the energy trapping in PSII; PI, performance indexes of PSII the distribution of DArT and SSR markers showed the highest saturation of R genome in contrast to the A and B genomes. Similar effect with the best coverage and highest density of R genome in triticale genetic maps were previously described by Tyrka et al (2011) and Karbarz et al (2020). Up to now, several genetic maps have been developed and reported QTL analysis in triticale (Alheit et al 2011;Badea et al 2011;González et al 2005;Tyrka et al 2011Tyrka et al , 2015Krzewska et al 2012Krzewska et al , 2015Dyda et al 2019;Karbarz et al 2020).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Magnat Abbreviations: ABS/CS, absorbed energy flux per leaf cross-section (CS); Tr 0 /CS, trapped energy flux in PSII reaction centers per leaf crosssection; ET 0 /CS, the energy flux for electron transport per leaf cross-section; ET 0 /RC, the energy flux for electron transport per the single, active PSII reaction center; F v /F m , yield of the energy trapping in PSII; PI, performance indexes of PSII the distribution of DArT and SSR markers showed the highest saturation of R genome in contrast to the A and B genomes. Similar effect with the best coverage and highest density of R genome in triticale genetic maps were previously described by Tyrka et al (2011) and Karbarz et al (2020). Up to now, several genetic maps have been developed and reported QTL analysis in triticale (Alheit et al 2011;Badea et al 2011;González et al 2005;Tyrka et al 2011Tyrka et al , 2015Krzewska et al 2012Krzewska et al , 2015Dyda et al 2019;Karbarz et al 2020).…”
Section: Discussionsupporting
confidence: 75%
“…Diversity Arrays Technology (DArT) used in our research is known as a tool used to construct genetic maps of many crop species (Wenzl et al 2004). That microarray technology can provide the information of several thousand sequence-specific markers without sequence information (Jaccoud et al 2001;Karbarz et al 2020). In our research, Table 5 Summary of QTL for Fv/Fm (the yield of the energy trapping in PSII), PI (performance indexes of PSII) and energy fluxes (RC per single, active PSII reaction center and CS per leaf cross-sec-tion) identified using CIM methods.…”
Section: Discussionmentioning
confidence: 97%
“…Qfr for loci common for recovery, survival and electrolyte leakage; Qchl for loci containing analyzed chlorophyll a uorescence parameters); Hewo × Magnat (hm), chromosome names (wheat A and B group, rye group R) and QTL number on the chromosome (1)(2)(3)(4). Within the localized QTLs, candidate genes associated with the analyzed traits were identi ed in silico as described in Karbarz et al (2020).…”
Section: Quantitative Trait Loci (Qtl) Analysis and Candidate Genes Identi Cationmentioning
confidence: 99%
“…Diversity Arrays Technology (DArT) used in our research is known as a tool used to construct genetic maps of many crop species(Wenzl et al 2004). That microarray technology can provide the information of several thousand sequence-speci c markers without sequence information(Jaccoud et al 2001;Karbarz et al 2020). In our research, the distribution of DArT and SSR markers showed the highest saturation of R genome in contrast to the A and B genomes.…”
mentioning
confidence: 99%
“…However, number of reports describing QTL regions and associated with them, candidate genes of resistance to Blumeria graminis in triticale is very limited(Karbarz et al 2020;Dyda et al 2021). Therefore, analysis of PM resistance in 'Hewo' x 'Magnat' triticale population can result in an unique set of QTL and candidate genes associated with powdery mildew resistance and respective molecular markers useful for molecular breeding.Powdery mildew caused by fungal pathogen Blumeria graminis (DC.)…”
mentioning
confidence: 99%